PENERAPAN MODEL COOPERATIVE LEARNING DENGAN TEKNIK INDEX CARD MATH BERBASIS IT DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA DAN PEMAHAMAN NILAI SEJARAH - Amrikasari, Noeranti; Warto, W.; Suryani, Nunuk (HISTORIKA, 2016)
The purpose of this study to analyze: 1) Application of a model of cooperative learning with index cards of math-based engineering of IT to improve students' critical thinking in class XI IPA at SMAN I Ngemplak Boyolali, 2) Application of a model of cooperative learning with index cards of math-based engineering of IT to improve understanding of the value of history in class XI IPA at SMAN I Ngemplak Boyolali. This research is a class action (classroom action research). This research was conducted with three cycles, each cycle consisting of four phases, namely: 1) planning action, 2) the implementation of the action, 3) observation, 4) reflection. Each cycle carried out at a basic competency. Data was collected in three ways, namely: 1) observation, 2) test, 3) questionnaire. Of the implementation of the action taken obtained objective tests of critical thinking in the first cycle 46.67%, 73.3% in the second cycle, the third cycle of 83.33%. And for the acquisition of critical thinking questionnaire in the first cycle, 65.05%, 70.72% in the second cycle, the third cycle of 81.03%. The results of test scores understanding of history in pre-cycle value of 26.6%, pre-test in the first cycle of 30%, post-test on the first cycle 43.33%, pre-test on the second cycle 67.74%, post-test on the second cycle 74.19 %, pre-test on the third cycle 74.19%, post-test cycle III 100%, and a minimum of 75. The results obtained completeness of the data showed an increase in the quality of teaching history in grade XI-2 which includes students' critical thinking and understanding of historical value. Based on these results it can be concluded that the use of cooperative learning models with index cards of math-based engineering IT can improve students' critical thinking and understanding of the value of history in class XI IPA at SMAN I Ngemplak Boyolali.